2015
DOI: 10.3945/jn.115.215525
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity and Excessive Gestational Weight Gain Are Associated with Components of Child Cognition1–3

Abstract: Although GWG may be important for executive function, maternal BMI has a stronger relation than GWG to both offspring intelligence and executive function. Our findings contribute to evidence linking maternal obesity to long-term child outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 48 publications
3
85
1
Order By: Relevance
“…Gestational weight gain, pre-pregnancy body mass index and offspring behavior and attention-deficit hyperactivity disorder symptoms. Unpublished manuscript 2015) 32. Unlike domain-specific cognition measurements, academic achievement synthesises how behavioural and cognitive problems impact real-life functioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational weight gain, pre-pregnancy body mass index and offspring behavior and attention-deficit hyperactivity disorder symptoms. Unpublished manuscript 2015) 32. Unlike domain-specific cognition measurements, academic achievement synthesises how behavioural and cognitive problems impact real-life functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational weight gain, pre-pregnancy body mass index and offspring behavior and attention-deficit hyperactivity disorder symptoms. Unpublished manuscript 2015)32 is important. There is concern that low weight gain, particularly among obese women, may impair an offspring's cognitive function 41.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that maternal pre-pregnancy obesity is associated with a lower cognitive function in children, but results are not consistent [49][50][51][52][53][54][55][56][57] . Total weight gain during pregnancy seems not be associated with childhood cognitive function [54,56,60] . However, a study among 5,191 mother-offspring pairs of term deliveries from the UK showed small positive associations of maternal weight gain in each trimester of pregnancy with IQ scores at 8 years of age, without remarkable differences in strength of the effect estimates for different periods of maternal weight gain [61] .…”
Section: Childhood Outcomesmentioning
confidence: 98%
“…Overweight and obesity affect 60% of women of childbearing age in the United States (Flegal, Kruszon‐Moran, Carroll, Fryar, & Ogden, ; Ogden, Carroll, Kit, & Flegal, ) and are associated with several adverse health outcomes for mothers and children (Gilmore, Klempel‐Donchenko, & Redman, ; Marchi, Berg, Dencker, Olander, & Begley, ). Recently, maternal prepregnancy body mass index (BMI) and gestational weight gain (GWG) have emerged as potentially modifiable risk factors for adverse child cognitive development (Hinkle, Albert, Sjaarda, Grewal, & Grantz, ; Hinkle, Sharma, Kim, & Schieve, ; Hinkle et al, ; Huang et al, ; Jo et al, ; Keim & Pruitt, ; Pugh et al, ; Pugh et al, ; Pugh et al, ). Several non‐mutually exclusive biological mechanisms are postulated to be involved in these associations.…”
Section: Introductionmentioning
confidence: 99%